Effectiveness of Learning Using Ethnomathematics Approach Assisted by Adobe Animate to Improve Understanding of Mathematical Concepts for Junior High School Students - Achmad Buchori; Jaka Wisnu Wardana; FX Didik Purwosetiyono (Universitas Islam Sultan Agung, 2022)
This study aims to determine the effectiveness of learning with an ethnomathematical approach assisted by Adobe Animate to improve understanding of mathematics concepts for junior high school students. The ethnomathematical object used in this study is the Arjuna temple in Banjarnegara. This research is quasi-experimental (quasi-experimental). The population in this study was class IX students of SMP Negeri 1 Wanadadi in the academic year 2022/2023, with the research sample being taken at random by two classes, namely class IX A as the experimental class and class IX C as the control class. The data was obtained through tests after being processed and tested with a one-sided test, a learning completeness test, and a simple linear regression test. The results of data analysis show that: (1) there are differences in concept understanding between students who use the ethnomathematical approach assisted by Adobe Animate and conventional learning; (2) the ability to understand concepts of students who use the ethnomathematical approach assisted by Adobe Animate achieves mastery learning; (3) there is an effect of activeness on the ability to understand mathematical concepts of students who use learning with an ethnomathematical approach assisted by Adobe Animate.